Abraham Kuyper en Marie du Toit oor vrouestemreg - C. Landman (In die Skriflig, 1993)
In the period between 1914 and 1921 three texts concerning Afrikaans women were published on women's suffrage: these texts were written by Abraham Kuyper (1914): a commission of the Synod of the Gereformeerde Kerke of South Africa with J.D. du Toit as a member of this commission (1920): and by J.D. du Toit's sister, Marie du Toit (1921). In this article these three texts are compared as to their contents. It is indicated that Kuyper's views against women's vote were taken over directly by the commission of the GKSA. The views of both Kuyper and the commission were strongly rejected by Marie du Toit in the light of her understanding of being both reformed and female.